2012
DOI: 10.1563/aaid-joi-d-10-00127
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Different Abutment Connection Designs on the Stress Distribution Around Five Different Implants: A 3-Dimensional Finite Element Analysis

Abstract: The stability of the bone-implant interface is required for the long-term favorable clinical outcome of implant-supported prosthetic rehabilitation. The implant failures that occur after the functional loading are mainly related to biomechanical factors. Micro movements and vibrations due to occlusal forces can lead to mechanical complications such as loosening of the screw and fractures of the abutment or implants. The aim of this study was to investigate the strain distributions in the connection areas of di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
45
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(54 citation statements)
references
References 17 publications
(18 reference statements)
3
45
0
1
Order By: Relevance
“…Concerning stress distribution, clinicians should consider the mechanical behavior of different implant connection types when selecting them, since the stress transmitted to the bone [3], and it is essential that the selected connection satisfactorily resists them [3,22]. The conical design has high stability and tends to dissipate less stress to the abutment screw when compared with external [23] and internal hexagon [3,5], improving fracture resistance.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Concerning stress distribution, clinicians should consider the mechanical behavior of different implant connection types when selecting them, since the stress transmitted to the bone [3], and it is essential that the selected connection satisfactorily resists them [3,22]. The conical design has high stability and tends to dissipate less stress to the abutment screw when compared with external [23] and internal hexagon [3,5], improving fracture resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Concerning the internal hexagon implants, Palmer et al [20] attested that these connections provided lower bone loss during the first 2 years of function. Biomechanical factors and stress distribution were evaluated through finite element analysis by simulated load under different connection and retention systems [22][23][24] ( Table 4). The external hexagon exhibited higher strain values than internal hexagon and Morse taper connection [23].…”
Section: Ih (N=2) 40×115 MMmentioning
confidence: 99%
See 1 more Smart Citation
“…Looseness of the abutment screw causes poor fit of the superstructure, and can lead to fracture of the abutment screw and superstructure damage or detachment, as well as fracture of the implant or resorption of the periimplant bone. A study using finite elements analysis reports that an implant system with external connection showed the highest stress values on the abutment screw and the implant-abutment connection during loading 18) . In loading tests and fracture tests, tube-in-tube implant connection systems are reported to show greater strength than systems with shallow connections 19) .…”
Section: Introductionmentioning
confidence: 99%
“…11 Marginal bone loss may be affected by factors such as characteristics of the implant platform surface 12,13 or the prosthetic connection. [14][15][16][17][18][19] Thus, stability of the connections among different parts of the implant also contributes to the longevity of the implant-supported prosthesis, particularly in single posterior restorations where a resilient interface between the abutment and the implant is necessary. 20 Some researchers have found that the configuration of the platform connections would reduce the stress concentration in the peri-implant bone.…”
mentioning
confidence: 99%